Regulatory authorities in the EU information and communications technology sectors: The role of trust and transparency in watching the watchdog - David Stevens (International Telecommunications Society (ITS), 2011)
Our research starts from the general observation that everywhere around the globe, an increasing number of regulatory tasks, traditionally falling under the responsibility of government, are being transferred to so-called independent regulatory authorities (i.e. independent from market actors, but quite often, also from political actors). This is, for instance, the case in the recently liberalized network industries (e.g. energy, railways), but also in the financial or the audiovisual media sector. In some cases (e.g. the electronic communications sector in the European Union), powers attributed to these regulatory authorities even prevent other, more democratically legitimate, institutions, like governments or parliaments, to interfere with the regulatory policy (cf. Judgment 424/07 of the Court of Justice in the German regulatory holidays case of December 3rd, 2009). Especially in that case, the question becomes: who's watching the watchdog?
Keywords: K23; K21; 330; Independent regulatory bodies; regulation; media and communications law